How Labor Values Affect Mental Health: An Analysis From the Perspective of Social Support - Gu, Yuliang; Chao, Xiaomei (Frontiers in Psychology, 2021)
To explore the positive and negative effects of labor values on mental health from the aspects of life satisfaction and psychological distress, and further verify the mediating role of social support. A total of 2691 primary and secondary school students were surveyed by Labor Values Scale, the Multidimensional Scale of Social Support, General Health Questionnaire and Satisfaction with Life Scale, and the results of which showed that: (1) Labor values can positively predict life satisfaction, while they are negatively correlated with psychological distress; (2) Social support can play a mediating role between labor values and life satisfaction; (3) Social support can also play a mediating role in the relationship between labor values and psychological distress. This study revealed that the specific path and mechanism of labor values on mental health. This provided a reference for families and schools to further implement the education of labor values on primary and secondary school students and helped to promote the social construction of an education system that aimed at cultivating individual all-round development.